The role of knowledge management in achieving competitive advantage: A case study of Djezzy, an Algerian telecommunications company - Saim, Abderrahmane; Mousli, Tayeb (Art Law and Accounting Reporter, 2025)
This study aims to identify the role of knowledge management in its various processes (knowledge acquisition, storage, transfer, and application) in achieving competitive advantage in its dimensions (quality, creativity, operational efficiency) at Djezzy Telecommunications Company in Algeria. To achieve the study objectives, a questionnaire was designed and developed, then statistically processed using the Statistical Package for the Social Sciences (SPSS.26). The study found a high level of respondents’ awareness of the practice level of knowledge management functions and the dimensions of competitive advantage at Djezzy, There is a statistically significant effect of knowledge management processes on the competitive advantage at Djezzy Telecommunications Company. The study recommended the necessity of increasing attention to knowledge management processes through the effective implementation of practices that enhance the knowledge acquisition process for employees.